Around the World in Eighty Days. Junior Deluxe Edition - Verne, Jules, 1828-1905 (Salt Lake City, UT : Project Gutenberg, 2000)
"Around the World in Eighty Days" by Jules Verne is an adventure novel first published in 1872. Wealthy London gentleman Phileas Fogg wagers half his fortune that he can circumnavigate the globe in exactly eighty days. Accompanied by his French valet Passepartout, Fogg races against time across continents by train, steamer, elephant, and sled. But a detective mistakenly believing Fogg is a bank robber pursues them relentlessly, threatening to derail their precisely calculated journey at every turn. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Around_the_World_in_Eighty_Days
Release date is 2000-04-01
Produced by Bill Stoddard
Keywords: Adventure stories; Voyages around the world -- Fiction